Graphene nanoplatelets–silver hybrid nanofluids for enhanced heat transfer - Yarmand, H.; Gharehkhani, S.; Ahmadi, G.; Shirazi, S.F.S.; Baradaran, S.; Montazer, E.; Zubir, M.N.M.; Alehashem, M.S.; Kazi, S.N.; Dahari, M. (Elsevier, 2015)
In the present experimental work, a new synthesis method is introduced for decoration of silver on the functionalized graphene nanoplatelets (GNP-Ag) and preparation of nanofluids is reported. The thermo-physical properties, heat transfer performance and friction factor for fully developed turbulent flow of GNP-Ag/water nanofluids flowing through a circular tube at a constant heat flux were investigated. GNP-Ag uniform nanocomposite was produced from a simple chemical reaction procedure, which includes acid treatment for functionalization of GNP. The surface characterization was performed by various techniques such as XRD, FESEM, TEM and Raman. The GNP-Ag nanofluids were prepared by dispersing the nanocomposite in distilled water without the assistance of a surfactant and/or ultrasonication. The prepared nanofluids were found to be stable and no sedimentation was observed for a long time. The experimental data for GNP-Ag nanofluids were shown improvements of effective thermal conductivity and heat transfer efficiency in comparison with the corresponding to the base-fluid. The amount of enhancement was a function of temperature and weight concentration of nanoparticles. Maximum enhancement of Nusselt number was 32.7% with a penalty of 1.08 times increase in the friction factor for the weight concentration of 0.1% at a Reynolds number of 17,500 compared to distilled water. Improved empirical correlations were proposed based on the experimental data for evaluation of Nusselt number and friction factor.